Beyond the Frontlines: 50 Days Since the Pahalgam Incident (Policy Perspectives)
This integrated set of policy briefs was developed in the wake of the critical inflection point in Pakistan’s security and strategic environment, Operation Bunyan-um-Marsoos. Each brief addresses a specific dimension of Pakistan’s evolving posture, collectively shaping a roadmap for national strategy, deterrence, stability, and regional engagement in the post-conflict phase.